Analisis dan Faktor yang Mempengaruhi Biaya Kemoterapi Pasien Kanker Payudara - heny dwi arini; Agustina Nila Yuliawati; Balqish Fathoum Medinna (LPPM Universitas Abdurrab, 2023)
The high incidence of breast cancer poses an economic burden to patients as well as the government due to expensive and periodic medical expenses. Therefore, a cost analysis is needed which can provide input for estimated costs to be incurred in the future. The purpose of this study was to determine cost estimates and factors that affect chemotherapy costs in breast cancer patients. Observational study with a cross-sectional design using data on treatment episodes for breast cancer patients during the 2022 period at X Hospital. The purposive sampling method was used by fulfilling the inclusion and exclusion criteria of the study. Retrospective data collection from medical records and patient billing. Data analysis included patient demographic characteristics, treatment cost calculations, and factors affecting costs with a multivariate linear regression test. The results showed that the highest average total cost of breast cancer chemotherapy at X Hospital for the 2022 period was IDR 34,040,751 at stage III class 1, and the factor that affected chemotherapy costs was age (p = 0.021).